Completeness of pediatric TB reporting in New York City. - San Gabriel P; Saiman L; Kaye K; Silin M; Onorato I; Schulte J (Public Health Reports)
OBJECTIVE: Accurate surveillance of tuberculosis (TB) in children is critical because such cases represent recent transmission, but surveillance is difficult as only 10% to 50% of cases are culture-confirmed. Hospital-based sources were used to develop alternative surveillance to assess completeness of reporting for pediatric TB in northern Manhattan and Harlem from 1993 through 1995. METHODS: Alternative surveillance sources included ICD-9-CM hospital discharge codes for active TB and gastric aspirate reports. Cases identified by alternative surveillance were compared with cases previously reported to the New York City Department of Health (NYC DOH). RESULTS: Alternative surveillance detected 25 cases of possible pediatric TB, of which four (16%) had never been reported to the NYC DOH and three (12%) had been reported as suspect cases, but had not fulfilled the criteria for a reportable case of pediatric TB. Of these seven newly counted cases, three were detected by ICD-9-CM codes, three by a gastric aspirate log book, and one by both. In contrast, 13 other cases had been reported to the NYC DOH, but were undetected by our alternative surveillance; eight of these could be verified with available medical records. Thus, the demographic and clinical characteristics of the 25 detected and the eight undetected cases with available medical records were evaluated in this study. CONCLUSION: Alternative surveillance proved effective, was complementary to the NYC DOH surveillance efforts, and increased the number of pediatric TB cases identified during the study period by 21%.